Effect of oil mass flow rate on temperature profile in oil wells - M Elfaghi, Abdulhafid; Ajaj, Wisam B.; Afolabi, Lukmon Owolabi (Akademia Baru Publishing, 2020)
In several design calculations including the development of programs to optimize production, engineers and scientists require accurate prediction of temperature drop due to flow in oil wells. The purpose of this research is to create mathematical models to predict the effect of oil mass flow rate on temperature distribution in oil wells. A numerical mathematical model is developed to study the parameters affecting the dynamic and static temperature profiles in oil wells in production and shutting operation. The temperature distribution of the oil from the reservoir to the surface and the temperature distribution in the wall tubing of the oil well and casing, cement sheaths, and surrounding formation is studied. The natural flow of oil wells in Alwahat area located 70 Kilometres south of Marada area east of Libya in the Zaggut field called (6Q1-59) is taken as a study case. In production case, different mass flow rates in winter and summer seasons are studied. The temperature profile in the horizontal direction is estimated at different depths. The Results show that the surface temperature of crude oil increases with the rise in mass flow rate.